The circular economy and its role in reducing environmental waste and promoting sustainability (Journal of Planner and Development, 2026)
The study explores how the principles and practices of a circular economy can help reduce the amount of waste in the environment and attain sustainability in Iraq. It examines the awareness of people on the environment, their level of knowledge and behavior, the influence of the infrastructure and local policies, and the identification of the most notable barriers and motivators to implementation. The research utilized a descriptive-analytic methodology in the questionnaire that was given to a sample of 270 people. The analysis of data was done on correlation coefficients and regression. The findings revealed excessively good and positive relationships between the knowledge of the circular economy, good environmental practices, and infrastructure evaluation. The outcomes also showed that there was a moderate negative correlation of the level of awareness and environmental practices and obstacles as well which mean that the minimization of obstacles is part of the process of encouraging the adoption of the circular economy. The regression analysis showed that awareness and infrastructure were the two variables that had the greatest impact on the environmental behavior that explained 96.6 and 96.3 percentage of the variance, respectively, and obstacles affected it negatively. The research suggests the establishment of environmental infrastructure, increasing the level of community awareness, and mobilizing supportive legislation and policies. The paper finds that one of the entry points to the reduction of waste and the creation of long-term environmental and economic sustainability in Iraq is the adoption of an integrated approach to the circular economy.